2022
DOI: 10.3390/ijms23052641
|View full text |Cite
|
Sign up to set email alerts
|

An Anthranilate Derivative Inhibits Glutamate Release and Glutamate Excitotoxicity in Rats

Abstract: The neurotransmitter glutamate plays an essential role in excitatory neurotransmission; however, excessive amounts of glutamate lead to excitotoxicity, which is the most common pathogenic feature of numerous brain disorders. This study aimed to investigate the role of butyl 2-[2-(2-fluorophenyl)acetamido]benzoate (HFP034), a synthesized anthranilate derivative, in the central glutamatergic system. We used rat cerebro-cortical synaptosomes to examine the effect of HFP034 on glutamate release. In addition, we us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
(66 reference statements)
0
6
0
Order By: Relevance
“… 41 The Chop, Grp‐78 and caspase‐12 are important endoplasmic reticulum stress biomarkers. 42 SVP administration significantly elevated the hepatic Chop, Grp‐78 and caspase‐12 protein levels, which was markedly inhibited by A. muciniphila MucT. These results indicated that anti‐endoplasmic reticulum stress is also an important mechanism for the protective effect of A. muciniphila MucT against SVP‐induced liver injury.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“… 41 The Chop, Grp‐78 and caspase‐12 are important endoplasmic reticulum stress biomarkers. 42 SVP administration significantly elevated the hepatic Chop, Grp‐78 and caspase‐12 protein levels, which was markedly inhibited by A. muciniphila MucT. These results indicated that anti‐endoplasmic reticulum stress is also an important mechanism for the protective effect of A. muciniphila MucT against SVP‐induced liver injury.…”
Section: Discussionmentioning
confidence: 79%
“…Endoplasmic reticulum stress is tightly linked to the liver injury of acetaminophen, isoniazid, SVP, etc 41 . The Chop, Grp‐78 and caspase‐12 are important endoplasmic reticulum stress biomarkers 42 . SVP administration significantly elevated the hepatic Chop, Grp‐78 and caspase‐12 protein levels, which was markedly inhibited by A. muciniphila MucT.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate release from synaptosomes was detected through a glutamate dehydrogenase reaction, as described previously [ 48 , 49 ]. Briefly, synaptosomes (0.5 mg/mL of final protein concentration) were incubated in HEPES-buffered medium containing glutamate dehydrogenase (20 U/mL) (Sigma, St. Louis, MO, USA), β-nicotinamide adenine dinucleotide (NAD + , 1 mM), and CaCl 2 (1.2 mM), at 37 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously [ 49 , 50 ], synaptosomes were resuspended in HEPES-buffered medium containing Fura-2-acetoxymethyl ester (5 μM) and CaCl 2 (0.1 mM) for 30 min at 37 °C. The synaptosome suspension was centrifuged (3000× g for 1 min), and the pellet was resuspended in HEPES-buffered medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation